REAKSI PASAR TERHADAP SAHAM IDX30 DI BURSA EFEK INDONESIA PADA SAAT PANDEMI COVID-19 MASUK DI INDONESIA - Shaan, Exodus; Dana, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024, 2024)
This study was conducted to analyze the market reaction to the latest infectious disease outbreak event which the spread of Covid-19 focused on abnormal returns and trading volume activity before and after the announcement of the first case of Covid-19 in Indonesia. This research was conducted on companies in the IDX30 Index. The population of this research is 30 issuer companies listed on the IDX30 Index. The research sample was determined by purposive sampling technique in order to obtain a sample of 27 companies. Data analysis was carried out by calculating abnormal returns and trading volume activity through the Paired Sample t-test Paired, and the Wilcoxon Signed Rank Test. The results showed that there was no significant differences abnormal return on the IDX30 Index before and after the announcement of the entry of the Covid-19 pandemic in Indonesia on the Indonesia Stock Exchange. Meanwhile, in trading volume activity, there are significant differences in the IDX30 Index before and after the announcement of the entry of the first case of the Covid-19 pandemic in Indonesia on the Indonesia Stock Exchange. There is a tendency for negative reactions or abnormal returns around the announcement of Covid-19, which can be used as a preference in the selection of shares, namely by buying shares by taking advantage of the decline in stock prices, until they reach the optimal point to be purchased, and releasing stocks that are predicted to cause losses in the long term.